P286 ECHOCARDIOGRAPHIC FINDINGS IN SUBJECTS WITH AN AMYLOIDOGENIC APOLIPOPROTEIN A1 MUTATION. (18th May 2022) - Aimo, A; Tomasoni, D; Lombardi, C; Panichella, G; De Angelis, M; Fabiani, I; Regazzoni, V; Vergaro, G; Nardi, M; Passino, C; Scolari, F; Emdin, M; et al.
Abstract: Background: The APOA1 gene encodes the precursor of apolipoprotein AI (ApoAI), whose mature form is the major component of high–density lipoproteins. APOA1 mutations may cause a form of hereditary amyloidosis (AApoAI). Only very small case series of patients with AApoAI are available. Methods: We examined 189 consecutive subjects with the heterozygous APOA1 Leu75Pro mutation referred for cardiac screening over a 10–year timespan at the Spedali Civili of Brescia (Italy). Results: Subjects (men 54%, median age 55 years, renal disease 39%, liver disease 31%) had a median left ventricular ejection fraction (LVEF) of 60% (55–66), did not display a prominent diastolic dysfunction (E/e' ratio 7 [6–10]) nor LV hypertrophy (LV mass index [LVMI] 92 g/m2 [74–111]). LV global longitudinal strain (GLS) (–19% [–21 to –17]), and mass to strain ratio (MSR) (10.0 [6.8–12.1]) were within normal limits. Age correlated with several echocardiographic parameters, including interventricular septal (IVS) thickness (r = 0.484), LVMI (r = 0.459), E/e' (r = 0.501), and right ventricular free wall thickness (r = 0.459) (all p < 0.001). Some individuals displayed echocardiographic red flags of cardiac amyloidosis (CA; "granular sparkling" of the IVS, 19%; pericardial effusion, 11%; apical sparing, 10%; thickened atrioventricular valves, 8%). Thirteen out of 96 (14%) fulfilled non–invasive criteria for CA. Twenty–nine subjects died over 5.8 years (4.1–8.0), with 10 deaths for cardiovascular causes; 14 out of 182 (8%) were hospitalized because of HF, and 17 (9%) died for cardiovascular causes or were hospitalized for HF. Individuals with suspected CA had a much higher risk of all–cause death (p = 0.009), cardiovascular death (p < 0.001), cardiovascular death or HF hospitalization (p < 0.001), and HF hospitalization alone (p < 0.001). Furthermore, subjects with either renal or liver involvement had a higher risk of events and a worse outcome. Conclusions: In subjects with an amyloidogenic APOA1 mutation, transthoracic echocardiography showed only minor signs of cardiac disease. The correlations between age and echocardiographic findings suggested a progressive increase in wall thickness, a decline in systolic and diastolic function, and a greater uncoupling between LV mass and contractility over time. Subjects with both renal and liver disease displayed the most evident signs of biventricular involvement and had a worse outcome.